Temperatura e nutrientes influenciam a estrutura de tamanho do fitoplâncton : variabilidade sazonal em lagos de inundação. - Iatskiu, Patrícia (2017)
Phytoplankton size has great influence on the functioning of aquatic ecosystems and is strongly controlled by environmental factors. It has been suggested that the global increase in temperature can be influence smaller body size. Ecological studies in environments of different latitudes allow the inclusion of temperature variation and provide an excellent opportunity to investigate the relationship between temperature and size. In this study, we used data of the subtropical and temperate lake to determine the drivers of the variation of phytoplankton size. We hypothesize that temperature is the main driver of this variation, and we expect that the smaller sizes are associated with higher temperatures. Quarterly samplings of two lakes, one located in a temperate region, in the floodplain of the Illinois River (40°20'46.14 "N and 90°01'29.56" W) and another in a subtropical region in the floodplain of the upper Paraná River - BR (22º43'S and 53º17'W), between 2008 and 2012. The size structure was evaluated through the biovolume and abundance ratio. Differences in size structure at different temperatures were tested using Kruskal-Wallis. The Akaike information criterion was used to investigate the predictive environmental drivers of the size structure. Larger average sizes were found at higher temperatures. The high variability of the environmental factors reflected a high variability in the size structure, which probably influenced the absence of significant differences. The temperature and nutrients was the main predictor variables for the phytoplankton size structure, however, the processes that control this structure varied between the temperate and the subtropical lake.